Tai chi : a step-by-step teaching plan with over 250 photographs - Popovic, Andrew (Lorenz Books, an imprint of Anness Publishing Ltd, 2021)
An expert guide to the popular, accessible Wu style, giving instructions on how to perform the short form with clear, step- by-step photographs.